1977
DOI: 10.1002/1097-4679(197701)33:1+<58::aid-jclp2270330111>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia as a function of non-affective interpretation of ambiguous stimuli and threshold for affective and neutral stimuli

Abstract: A theory that schizophrenic anhedonia-the failure to express pleasure-is associated with a tendency to interpret ambiguous stimuli as neutral rather than emotion-laden and arises from selectively high perceptual thresholds for affective stimuli was tested. Seventy-six schizophrenic males were required to guess whether words presented to them tachistoscopically for extremely short periods were positive, negative or neutral in content. The high-anhedonic Ss were significantly more likely to guess neutral words a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…Only a small amount of research on anhedonia has appeared. Watson (1977) found anhedonia associated with tendencies to perceive ambiguous stimuli as emotionally bland, but other studied hypothesized etiological factors-deficient neurological pleasure centers (Watson, 1972a), low physiological arousal (Watson, 1972b), high stimulation threshold (Watson, 1972b), social aversiveness (Watson, 1972a), selective perception (Watson, 1977) and selective attention to emotional stimuli (Watson & Jacobs, 1976)-have yielded negative results. Zuckerman and his associates (1971) have produced a substantial body of research on the correlates of sensation-seeking, but the present authors are unaware of any research on its origins.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Only a small amount of research on anhedonia has appeared. Watson (1977) found anhedonia associated with tendencies to perceive ambiguous stimuli as emotionally bland, but other studied hypothesized etiological factors-deficient neurological pleasure centers (Watson, 1972a), low physiological arousal (Watson, 1972b), high stimulation threshold (Watson, 1972b), social aversiveness (Watson, 1972a), selective perception (Watson, 1977) and selective attention to emotional stimuli (Watson & Jacobs, 1976)-have yielded negative results. Zuckerman and his associates (1971) have produced a substantial body of research on the correlates of sensation-seeking, but the present authors are unaware of any research on its origins.…”
supporting
confidence: 81%
“…I n this respect they complement two earlier studies in which anhedonia and sensation-seeking deficit were found to be unrelated to threshold for, and selective attention to, stimuli varying in emotional quality (Watson, 1977;Watson & Jacobs, 1976).…”
Section: Discussionmentioning
confidence: 98%